Production and Evaluation of Biodiesel from Sheep Fats Waste - Salih Abbas, Ammar; Salah Othman, Toleen (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
Animal fats are a good, promising and ethical alternative source for biodiesel production, but they need more complex treatments than vegetable oils. Iraqi butchery plants waste fats (sheep fat) which are suggested as feedstock to produce biodiesel. This type of fat contains a large quantity of free fatty acids (FFAs) (acid number 49.13 mg KOH/g of fat). The direct transesterification of such fats produce high amount of soap instead of desired biodiesel, so a pre-treatment step (to reduce FFAs) is necessary before transesterification. This step was done by esterification of the free fatty acids in the fat by adding ethanol and using 1% acid catalyst (H2SO4) for 30 minutes. The results showed that the acid number of sheep fat after pre-treatment step reduced to 0.97 mg KOH/g of fat at esterification step. Transesterification of treated fats (produce from esterification) used to convert biodiesel. The maximum yield of biodiesel was about 85 vol. % for treated fats obtained with 25/100 ethanol/fat wt. ratio, 70° C reaction temperature and 50 minutes total treatment period (pre-treatment step and transesterification reaction). The suggested model of the production rate kinetic of transesterification reaction, found that the production rate is inversely proportional with the volume of biodiesel produced with activation energy of 25320 J/mole.